Improving psychotherapy effectiveness by addressing the problem of premature termination: Introduction to a special section. (3rd September 2018) - Swift, Joshua K.; Spencer, Julie; Goode, Jonathan
Abstract: Premature termination appears to be a consistent problem in psychotherapy, showing up across client, treatment, and therapist types. As psychotherapy researchers and practitioners, it is important that we gain a better understanding of this negative psychotherapy event and identify methods for reducing its occurrence. This article introduces a special section on premature termination in psychotherapy. In addition to briefly introducing the articles contained in the special section, this article offers suggestions for future research on the topic of premature termination.